Neutrophil extracellular traps as an important part of the pathogenesis of chronic rhinosinusitis without polyps - Valery М. Svistushkin; Galina N. Nikiforova; Boris V. Pinegin; Nina V. Vorobjeva; Artem S. Dekhanov; Yulia A. Dagil; Anna R. Mironova (Consilium Medicum)
Background. Chronic sinusitis occurs in the Russian Federation in 16.4±10.89% of the population and has a great impact on the quality of life of patients. The inflammatory process underlying this pathology is often resistant to conservative treatment and causes surgical intervention. The study of the role of neutrophil extracellular traps as an important part of the immune response, as well as the capabilities of drugs capable of influencing the processes of netosis, is an important and relevant area of modern research.